1995
DOI: 10.1007/bf00197324
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and metabolism of abscisic acid in tomato leaves infected with Botrytis cinerea

Abstract: Abstract. Two virulent strains of Botrytis cinerea Pers., one of them (Bc 6) producing abscisic acid (ABA) via l',4'-trans-dioi-ABA in defined liquid culture, and a second strain (Bc 9) without the ability to form ABA or its fungal precursor, and two near-isogenic lines of tomato were used to study the biosynthesis and metabolism of ABA in infected isolated leaves. The tomato plants used were Lycopersicon esculentum Mill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 22 publications
2
45
0
3
Order By: Relevance
“…Some phytopathogenic organisms are known to produce ABA, including fungal pathogens such as Cercospora spp., Ceratocystis spp., Fusarium spp., Rhizoctonia spp., B. cinerea and M. grisea (Assante et al 1977;Dörffling et al 1984;Jiang et al 2010). Kettner and Dörffling (1995) showed that at least four processes can control ABA levels in tomato leaves infected with B. cinerea: (1) stimulation of fungal ABA biosynthesis by the host; (2) release of ABA or its precursor by the fungus; (3) stimulation of plant ABA biosynthesis by the fungus and (4) inhibition of ABA catabolism by the fungus. In addition, ABA was shown to accumulate in the hyphae and conidia of M. grisea and was also detected in culture filtrate indicative of ABA secretion (Jiang et al 2010).…”
Section: Aba-sa Antagonismmentioning
confidence: 99%
“…Some phytopathogenic organisms are known to produce ABA, including fungal pathogens such as Cercospora spp., Ceratocystis spp., Fusarium spp., Rhizoctonia spp., B. cinerea and M. grisea (Assante et al 1977;Dörffling et al 1984;Jiang et al 2010). Kettner and Dörffling (1995) showed that at least four processes can control ABA levels in tomato leaves infected with B. cinerea: (1) stimulation of fungal ABA biosynthesis by the host; (2) release of ABA or its precursor by the fungus; (3) stimulation of plant ABA biosynthesis by the fungus and (4) inhibition of ABA catabolism by the fungus. In addition, ABA was shown to accumulate in the hyphae and conidia of M. grisea and was also detected in culture filtrate indicative of ABA secretion (Jiang et al 2010).…”
Section: Aba-sa Antagonismmentioning
confidence: 99%
“…The extraction and purification was done following the method of Kettner et al (1995). The extraction was done at 4°C till 72 h in dark with a subsequent change of solvent at each 24 h. The extracted sample was centrifuged at 10,000 rpm and the supernatant was reduced to the aqueous phase using a rotary thin film evaporator at 35°C.…”
Section: Relative Water Content Of Leavesmentioning
confidence: 99%
“…Similarly, the involvement of ABA in plant-pathogen interactions is ambiguous. Increased endogenous levels of ABA were observed in response to infection by viruses, bacteria, and fungi (Steadman and Sequeira, 1970;Whenham et al, 1986;Kettner and Dorffling, 1995). The application of ABA induced callose deposition, resulting in resistance against necrotic fungi (Ton and Mauch-Mani, 2004;Mauch-Mani and Mauch, 2005).…”
Section: Introductionmentioning
confidence: 99%